Pengaruh Green Motive Terhadap Green Product Innovation Performance pada IKM Batik Ramah Lingkungan di Jawa Timur - Rahayu, Rahayu; Armin, Rini; Heru Dwihandoko, Toto (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This empirical study tests the hypothesis using a questionnaire survey to explore the positive influence of green motives on green product innovation performance on environmentally friendly batik SMEs in East Java. This study examines instrumental, relational, and moral motives and reveals that motives instrumental is a stronger driver than moral motives, while relational motives have no significant effect. Interesting hypothesis test results in this research, sEmpirically, if studied, there is a lack of understanding among stakeholders in detail about environmentally friendly batik that meets standards, especially for communities living in batik SME centers. There is a lack of strong social legitimacy in the environment around batik SMEs. This causes the weakness of batik SMEs to gain competitiveness in national and international markets. However SMEs have a fairly high level of concern for the environment without the support of stakeholders. This study also determines that moral motives have a positive influence on environmentally friendly product innovation performance. This research suggests that environmentally friendly batik SMEs must continue to develop green products so that the business they run can be sustainable and balanced with environmental sustainability.